Catalytic dehydrogenation of hydrogen-rich liquid organic hydrogen carriers by palladium oxide supported on activated carbon. (1st September 2020) - Shuang, Huili; Chen, Hao; Wu, Fei; Li, Jing; Cheng, Chen; Li, Haigang; Fu, Jie
Graphical abstract: Highlights: PdO was used as active site for dehydrogenation of hydrogen-rich liquid hydrogen carriers at low temperature. The oxidation state of Pd exhibited significant improvement in comparison to Pd 0 . PdO/AC showed a conversion of 100% with a yield of 95.8% at 100 °C for 60 h. Abstract: The dehydrogenation of organics, e.g., dodecahydro-N-ethylcarbazole (12H-NECZ), at temperatures lower than 150 °C, plays a particularly important role in H2 carriers by reducing energy consumption but remain a technical challenge. However, the dehydrogenation has currently been achieved using Pd-based catalysts at temperatures over 170 °C for 1.6 h. In this work, we reported a new strategy of using PdO as the active site, which can remarkably lower the dehydrogenation temperature compared with Pd o state. The dehydrogenation of hydrogen-rich liquid organic hydrogen carriers (HR-LOHCs) catalyzed by 10 wt% PdO/AC showed a 95.8% yield of total dehydrogenated liquid organic hydrogen carriers (LOHCs) at only 100 °C for 60 h, and, as a comparison, 60.9% yield of LOHCs were obtained over 10 wt% Pd/AC at the same reaction conditions for 96 h. Notably, an almost complete yield of LOHCs (95.3%) was achieved at 140 °C for 8 h using PdO/AC.